A staff-initiated quality improvement project: from paper to web report - Daphne Acebron Clemente; Nurul Amiella Abdullah; ZurianahJusmin Jasmin; Muhammad Syafiq Abdullah; Helen Benedict Lasimbang; Wendy Diana Shoesmith; Loo, Jiann Lin; Pang, Nicholas Tze Ping (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Continuous quality improvement of system is essential to improve efficiency of working environ¬ment. Limited financial allocation in low resource setting results in the vicious circle of having inadequate money to purchase a new system and print paper documents that are required for the operation of clinic. A staff-initiated system improvement with the name of “PRW UMS Staff Portal” was attempted to break-free from the vicious cycle. Methods: An online system covering different aspects of routine clinical work of healthcare workers was created in Dec 2019 and implemented in Feb 2020 using Google SiteTM by the nurses of a local university community clinic, which included: submission of daily reports of nurses and assistant medical officers, submission of reports of all programmes conducted by the clinic, surveillance of health status of working staffs, announcement and request of working roster, archiving of documents, and medication inventory. The system could only be accessed using official working email for general documents while accesses to sensitive documents were restricted to relevant staffs to pro¬tect privacy and confidentiality of information. Qualitative interviews were performed with all nursing staff involved. Results: Qualitative feeling of improvement in coordination of workflow was reported by all 23 staffs working in the clinic in view of the easy access of system using smartphone and computer at workstation. It also reduced the need to move away from the working station in order to access, replenish, or submit the printed documents and reports. Significant amount of paper and printing were saved monthly. Conclusions: Despite positive feedback from the staffs, the system requires further improvement in terms of function and security. Further evaluation on cost-efficiency of the system can be done to promote the system to other universities.